Mixed Convection from A Cylinder with Low Conductivity Baffles in Cross-Flow - A/K Abu-Hijleh, Bassam (2002)
The problem of laminar mixed convection from an isothermal cylinder with low conductivity baffles in cross flow was solved numerically. The average Nusselt number was calculated at different combinations of number of baffles, baffle height, Reynolds number, and buoyancy parameter. The reduction in the Nusselt number is as much as 75 percent. When using a small number of baffles at low values of buoyancy parameter, an odd number of baffles reduced the Nusselt number more than an even number of baffles, especially at high values of Reynolds number. This is not the case at high values of buoyancy parameter. There is an optimal baffle height, Reynolds number dependent, for maximum heat transfer reduction beyond which an increase in baffle height does not result in further decrease in heat transfer.